Processo de trabalho da estratégia de saúde da família na produção do cuidado ao idoso com diabetes Mellitus: o olhar de quem cuida e de quem é cuidado - Oliveira, Aline Neves (2015)
This study addresses the working process of the Family Health Strategy to provide care to the elderly with Diabetes Mellitus. It aims at analyzing the work process of the teams of the Family Health Strategy to provide carré too lhe elder with Diabetes Mellitus, in viés off Public. Police for lhe Elder Health, knowing the vision of team members and the elderly enrolled in the respective units. This is a qualitative study using Hermeneutic-dialectic. The techniques for data collection were the focus groups for 34 professionals from the Family Health Strategies and unstructured interviews to ten participants elderly. The content analysis elucidated two empirical categories: walking the elderly with Diabetes Mellitus in the Network Health Care, with a subcategory that addresses the accessibility and the flow of care in service. The second category refers to care for the elderly with Diabetes Mellitus: the real to the ideal and has two subcategories: the resistance model of biomedical care and the process of work in Health Strategy for the Family and the elderly with Diabetes Mellitus. The analytical from the categories was based on the theoretical axes, comprising the work process in health and public policy of health care for the elderly. The results show that the process of work in the Family Health Strategy for the care of these users, is sustained in biomedical optics and technical activities, with fragile accessibility, overlap of spontaneous demand, length and limitations during walking the elderly in the network, further development for curative actions to the detriment of health promotion, centrality of the working process on the medical professional, prescriptions and excessive referrals to secondary care sector, absence of risk classification and discourage self-care. As for the relationship between professionals and users, its primary for continuous and comprehensive care, these show up verticalized and imposition of scientific knowledge. In addition, the motivation, temporary contracts, the overhead and income inequality are responsible for driving the high turnover of professionals, triggering important clinical and managerial problems, as the formation of bonds and the excessive system costs related to new hires. Such perceived characteristics, through the testimonies of elderly and contradict the public policy of health care for the elderly and other policies governing the care of the Health Care Network. Thus, it is possible to infer that the model of biomedical attention lingers in the care the Family Health Strategies investigated, although there have been many efforts to break this paradigm. Of note is required the transformation of the work process in terms of its centrality and objectives, through the broad understanding of chronic health conditions, professional development and strengthening of primary care as coordinator of the network.